The risk-driven business model : four questions that will define your company - Girotra, Karan; Netesin, Sergej, 1973- (Harvard Business Review Press, 2014)
"Innovation isn't always about new products or services. In fact, many new ideas are realized--and then brought to market--thanks to a disruptive business model that challenges the conventional operating logic of an industry. In The Risk-Driven Business Model, Karan Girotra and Serguei Netessine--both professors at INSEAD--introduce a toolkit to help innovators better conceive the disruptive business models that create wealth and revolutionize industries. In the book, they outline how to transform a company by revisiting the assumptions around the firm's key decisions. Business model innovation, the authors say, essentially is about WHAT key decisions get made in a business, WHEN they get made, WHO makes them, and WHY those individuals make the decisions they do. So by changing a company's approach to these choices, you can fundamentally alter the risks involved and invent new, superior business models. Girotra and Netessine also describe the kinds of processes companies should have in place to help them imagine and explore these changes. With numerous examples of well-known companies in many different countries that are using the framework, this book serves as a toolkit for anyone--from entrepreneurs to executives--involved in the dynamic decisions that move industries forward"--Resumé vydavatele
Keywords: strategický management; podnikatelské projekty; organizační změna; strategic planning; business planning; organizational change; monografie; monographs